2017
DOI: 10.20524/aog.2017.0215
|View full text |Cite
|
Sign up to set email alerts
|

Nab-paclitaxel as second-line treatment in advanced gastric cancer: a multicenter phase II study of the Hellenic Oncology Research Group

Abstract: Background:This study evaluated the safety and efficacy of nab-paclitaxel as second-line treatment in patients with advanced gastric adenocarcinoma.Methods:Thirty-nine pretreated patients [33 with taxane-based regimens (docetaxel, cisplatin, and fluorouracil)] and 6 with combination of fluoropyrimidines plus cisplatin with locally advanced inoperable and metastatic gastric and gastroesophageal junction adenocarcinoma were treated with weekly nab-paclitaxel (150 mg/m2 d1, d8, d15 in cycles of 28 days).Results:P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…5 d). Studies have shown that nab-paclitaxel as second-line treatment in locally advanced inoperable or metastatic gastric and gastroesophageal junction carcinoma is a promising chemotherapy regimen [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 d). Studies have shown that nab-paclitaxel as second-line treatment in locally advanced inoperable or metastatic gastric and gastroesophageal junction carcinoma is a promising chemotherapy regimen [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…22 It has been studied intravenously in many solid tumours, including four phases II clinical trials for recurrent ovarian cancer [23][24][25][26] and in two phases II and a phase III trial for recurrent gastric adenocarcinoma. [27][28][29][30] IP administration of paclitaxel is a standard therapy for advanced epithelial ovarian carcinoma in North America, 31 but the IP administration of nabpaclitaxel has been little studied. IP administration of nab-paclitaxel has been evaluated in phase I trial in 27 patients with gynaecological and digestive PC, with an IP MTD of 140 mg/m 2 .…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Nab-paclitaxel has fewer side effects, shows increased tumour cell cytotoxicity, and patients have higher overall response rates, compared with equal doses of solvent-based paclitaxel in many solid malignancies 22. It has been studied intravenously in many solid tumours, including four phases II clinical trials for recurrent ovarian cancer23–26 and in two phases II and a phase III trial for recurrent gastric adenocarcinoma 27–30. IP administration of paclitaxel is a standard therapy for advanced epithelial ovarian carcinoma in North America,31 but the IP administration of nab-paclitaxel has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…GNPs-RNA conjugates are used in the coloriometric detection of biomarker micro-RNA in GC [ 147 ]. In the treatment of advanced GC and its metastasis, evidence indicates the improved effectiveness of nab-PAX [ 148 , 149 ]. These formulations could be used to increase the therapeutic value of the drugs by increasing the solubility.…”
Section: Np-based Gi Carcinoma Therapiesmentioning
confidence: 99%